PENGARUH KEPEMIMPINAN PARTISIPATIF DINASIPEMUDAIOLAHRAGAIDANIPARIWISATA TERHADAP PENGEMBANGAN OBJEKIWISATA ANJUNGAN KABUPATEN ENREKANG - Adnan Rifaldi; Muhammad Ikbal; Hariyanti Hamid (JIA: Jurnal Ilmiah Administrasi, 2022)
The aims of this research are to participatory leadership of the Youth, Sports and Tourism Office on the Development of Pavilion Tourism Objects, Enrekang District, Enrekang district, Galonta Villagei. Theipopulationiin thisistudyiwere 47 employeesiatithe Department of Youth, Sports and Tourism with sampling using the saturated sample formula so that Obtained a sample of 47 people . This type of research is descriptive and quantitative. Data collection techniques used in this study were observation, questionnaires, and literature study. The data analysis technique used is the IBM SPSS Statistics 21.0 application. Theiresults ofithisistudyiindicateithat the influence of participatory leadership with a percentage of 61.4% has a good effect. The development of the Pavilion tourist attraction with a percentage of 50.1% is not good. The influence of leadership "Influential/Significant" onithe development ofithe tourist attraction ofithe platform ofithe Enrekang sub-district, Enrekang district, Galonta village withia valueiof ticount titable or 3.,331 ≥ 2,212 with an influence percentage of 19.8%, so the influence of participatory leadership ofithe youthsports anditourism officeion the development of the object Pavilion tourism in Gallonta Village, Enrekang District, Enrekang Regency has not been effective.